Detecção molecular de Brucella abortus, Toxoplasma gondii e Leshmania spp. em felídeos silvestres de vida livre e de cativeiro no estado de Mato Grosso - Brasil - Kagueyama, Francielle Cristina (2022)
Most emerging infectious diseases are predominantly zoonoses, most of which are of wild origin. Wild felids play an important role in the epidemiology of pathogens that can affect the health of both domestic and wild animals and human health, serving as reservoir hosts. Thus, the objective was to diagnose through the molecular technique of PCR (Polymerase Chain Reaction) the species of B. abortus, T. gondii and Leishmania spp. in blood samples from wild and captive wild felids from the State of Mato Grosso, Brazil. Twenty-three blood samples from 6 species of wild felids (Leopardus colocolo, Leopardus pardalis, Leopardus wiedii, Pantera onca, Puma concolor and Puma yagouaorundii) were tested. B. abortus was detected in 4.34% (1/23), a captive Puma concolor. T. gondii was present in 13.04% of the felids (3/23), being 2 free-living animals (Leopardus colocolo and Leopardus pardalis) and 1 captive animal (Puma concolor). Leishmania spp. 8.69% of the felids were present (2/23), being 2 free-living animals (Leopardus pardalis and Puma concolor). The results obtained demonstrate that the microorganisms B. abortus, T. gondii and Leishmania spp. are present in wild felids. These animals play an important role in the ecological function, since they are carriers of infectious pathogens even without the development of clinical disease. The detection in captive and freeliving animals demonstrates the importance of monitoring related to zoonotic etiological agents, so that appropriate therapeutic and prophylactic measures can be adopted.